Macrolide Resistance Genes in Enterococcus spp. - Portillo, Aránzazu (American Society for Microbiology, 2000)
Seventy-eight isolates of different Enterococcus species (E. faecalis, n = 27; E. faecium, n = 23; E. durans, n = 8; E. avium, n = 6; E. hirae, n = 9; E. gallinarum, n = 3; and E. casseliflavus, n = 2) with a variety of erythromycin resistance phenotypes were examined for the presence of macrolide resistance genes (ermA, ermB, ermC, ermTR, mefA/E, and msrA). Positive PCR amplifications of ermB were obtained for 39 of 40 highly erythromycin-resistant Enterococcus isolates (MICs, >128 μg/ml) of different species; the remaining highly resistant E. faecium isolate was positive for PCR amplification of ermA but was negative for PCR amplification of the ermB and ermC genes. For all enterococcal strains for which erythromycin MICs were ≤32 μg/ml PCRs were negative for erm methylase genes. For all E. faecium isolates PCR amplified products of the expected size of 400 bp were obtained when msrA primers were used, with the results being independent of the erythromycin resistance phenotype. All the other enterococcal species gave negative results by msrA PCRs. Sequencing of the msrA PCR products from either erythromycin-susceptible, low-level-resistant, or highly resistant E. faecium strains showed that the amplicons did not correspond to the msrA gene described for Staphylococcus epidermidis but corresponded to a new putative efflux determinant, which showed 62% identity with the msrA gene at the DNA level and 72% similarity at the amino acid level. This new gene was named msrC.